Environment-friendly calcium-zinc composite heat stabilizer and preparation method thereof
Through the combination of auxiliary thermal stabilizer with zinc stearate and calcium stearate and modified organic acid intercalation hydrotalcite and modified silica, the problem of heavy metal pollution in PVC thermal stabilizer is solved, and the problem of improved The thermal stability and compatibility of PVC realize the application of environmentally friendly thermal stabilizers.
Patent Information
- Application Number
- CN202411451289.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-03
AI Technical Summary
The existing PVC thermal stabilizers contain heavy metals, which pollute the environment and endanger human health. They have poor thermal stability and light resistance, making it difficult to meet the requirements of different processing technologies and products.
Use auxiliary heat stabilizers to combine with zinc stearate, calcium stearate, etc., and use modified organic acid intercalation hydrotalcite and modified silica as auxiliary stabilizers to treat expanded vermiculite and dioxide through modification. Silicon improves the absorption of HCl by composite heat stabilizer and improves PVC compatibility, thereby improving the thermal stability performance of PVC.
It effectively improves the thermal stability of PVC, extends its long-term thermal stability, and reduces waste utilization. It uses environmentally friendly materials to be non-toxic and pollution-free, and improves the compatibility between hydrotalcite and PVC.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat stabilizers, in particular to an environmentally friendly calcium-zinc composite heat stabilizer and a preparation method thereof. Background Art
[0002] Polyvinyl chloride (PVC) is widely used in many fields such as building materials, pipes, coatings, industry, agriculture, etc. due to its excellent processing performance, corrosion resistance, flame retardancy and mechanical properties. However, PVC has poor thermal stability and light resistance. It will decompose and release hydrogen chloride at 140°C. However, the processing temperature of PVC is usually between 160-200°C to form. This causes PVC to degrade during processing, causing the product to change color and accompanied by performance degradation, greatly reducing its use value. At present, the main method to improve the thermal stability of PVC during processing is to add heat stabilizers to delay the degradation of PVC.
[0003] On the market, heat stabilizers can be divided into five categories, including lead salt stabilizers, metal soap stabilizers, organic tin (antimony) stabilizers, rare earth composite stabilizers and other types of stabilizers. PVC heat stabilizers usually contain heavy metals such as Pb, Cr, Cd, etc., which pollute the environment and endanger human health. Among them, calcium zinc heat stabilizers in metal soap heat stabilizers have the advantages of environmental protection, non-toxicity, good lubricity, and low price. In application, they have a strong ability to absorb HCl generated during the PVC processing process, thereby improving the long-term stability of PVC. Although calcium zinc heat stabilizers can improve the thermal stability of the PVC processing process, in order to meet the requirements of different processing technologies and different products, further research on calcium zinc heat stabilizers is needed. The use of auxiliary heat stabilizers and calcium zinc heat stabilizers in combination is the current mainstream research direction. Summary of the invention
[0004] The purpose of the present invention is to provide an environmentally friendly calcium-zinc composite heat stabilizer and a preparation method thereof, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions: An environmentally friendly calcium-zinc composite heat stabilizer comprises the following raw materials, measured by weight: 10-20 parts of zinc stearate, 20-30 parts of calcium stearate, 10-15 parts of auxiliary stabilizer, 5-8 parts of plasticizer, 1-5 parts of antioxidant and 2-5 parts of filler.
[0006] Preferably, the auxiliary stabilizer comprises β-diketone, modified organic acid intercalated hydrotalcite and modified silica, and the mass ratio of β-diketone, modified organic acid intercalated hydrotalcite and modified silica is 1:3:(1-3).
[0007] Preferably, the filler is one or more combinations of zeolite, talc, zinc carbonate and calcium carbonate.
[0008] The preparation steps of the modified organic acid intercalated hydrotalcite include: S1): Take expanded vermiculite, place it in deionized water, add nitric acid solution after high-speed shearing, react in a 95°C oil bath for 8-12 hours, perform solid-liquid separation, dry the separated silicon dioxide for later use, and collect the supernatant; S2): Take the supernatant collected in S1, add zinc nitrate and lanthanum nitrate, and then sonicate and stir to obtain a nitrate solution; dissolve the organic acid in anhydrous ethanol, mix the sodium hydroxide solution and the sodium bicarbonate solution, and dropwise add the nitrate solution. After the dropwise addition, centrifuge to take out the precipitate, wash it with deionized water until it is neutral, place it in deionized water with sonication, perform hydrothermal reaction, react at 120-180°C for 8-12h, filter, wash, and dry to obtain an organic acid intercalated hydrotalcite; S3): Take S2 organic acid intercalated hydrotalcite and place it in deionized water for ultrasonic treatment, add a modifier, stir it at 60°C for 2-3h, filter and wash it, grind it, and obtain a modified organic acid intercalated hydrotalcite.
[0009] Preferably, the organic acid in S2 is any one of itaconic acid, maleic acid, cinnamic acid and citric acid.
[0010] Preferably, the modifier in S3 is any one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium stearate and sodium citrate.
[0011] The preparation steps of modified silica include: taking the dried silica prepared in S1 and placing it in a KH550 alcohol solution for ultrasonic dispersion for 30-40 minutes, then heating it to 80°C for reaction for 8-10 hours, vacuum filtering, washing and drying, placing it in a tetrahydrofuran solvent, adding maleic anhydride and mixing evenly, mechanically stirring at 70-90°C for 3-5 hours, continuing to heat to 160°C, adding pentaerythritol and reacting for 2 hours, rotary evaporating to remove tetrahydrofuran, washing and drying, and obtaining modified silica.
[0012] Preferably, the molar ratio of KH550, maleic anhydride and pentaerythritol is 1:1:1, and the amount of KH550 used is 4-5wt% of the silicon dioxide.
[0013] A method for preparing an environmentally friendly calcium-zinc composite heat stabilizer comprises the following steps: mixing an auxiliary stabilizer and a filler, stirring at a rotation speed of 100-200 rpm for 10-30 min, adding an antioxidant and a plasticizer, increasing the rotation speed to 300-400 rpm, continuing stirring for 5-10 min, adding zinc stearate and calcium stearate, increasing the rotation speed to 400-600 rpm and stirring for 30-40 min, and obtaining the calcium-zinc composite heat stabilizer.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adopts an auxiliary heat stabilizer and zinc stearate, calcium stearate and the like to prepare a calcium-zinc composite heat stabilizer, which synergistically improves the heat stabilizer to absorb hydrogen chloride released by thermal degradation of PVC, thereby further improving the thermal stability of PVC; 2. The auxiliary stabilizer used in the present invention is composed of β-diketone, modified organic acid intercalated hydrotalcite and modified silica in a certain proportion; wherein the modified organic acid intercalated hydrotalcite is obtained by splitting expanded vermiculite, and zinc and lanthanum are added to the supernatant of solid-liquid separation, combining the advantages of hydrotalcite and rare earth elements to effectively inhibit the release of hydrogen chloride, and organic acid intercalation and modifier are added to improve the dispersibility, improve the compatibility of hydrotalcite with PVC and extend the long-term thermal stability of PVC. The raw material of modified silica is a solid substance obtained by splitting expanded vermiculite to obtain solid-liquid separation, which is modified by a silane coupling agent and then reacted with maleic anhydride to undergo an acylation reaction to obtain an acid group that undergoes an esterification reaction with pentaerythritol. While improving the compatibility of silica and pentaerythritol with PVC, pentaerythritol, as an excellent auxiliary thermal stabilizer, brings a good HCl absorption effect to the composite thermal stabilizer; 3. The present invention selects expanded vermiculite to be decomposed to obtain hydrotalcite and silicon dioxide, which are added into the composite stabilizer to improve the utilization rate of vermiculite and reduce waste; the organic acids used in the intercalated hydrotalcite are all environmentally friendly materials, non-toxic and harmless. DETAILED DESCRIPTION
[0015] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0016] In the experiment, epoxidized soybean oil was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with the product number E107074; expanded vermiculite with a specification of 200-800 mesh and zeolite with a specification of 200-800 mesh were both purchased from Lingshou County Nanyu Mineral Products Processing Plant; PVC resin powder SG-5 and PVC paste resin PB 108-2 were both purchased from Kunshan Chaoheng Plastic Co., Ltd.
[0017] The KH550 alcohol solution is obtained by mixing water, ethanol and KH550 in a mass ratio of 10:88:2.
[0018] Example 1: A method for preparing an environmentally friendly calcium-zinc composite heat stabilizer, comprising the following steps: Take 10 parts of auxiliary stabilizer and 3 parts of zeolite, mix them, stir at 100 rpm for 10 minutes, add 3 parts of phosphite and 6 parts of epoxidized soybean oil, increase the speed to 400 rpm, continue stirring for 10 minutes, then add 20 parts of zinc stearate and 30 parts of calcium stearate, increase the speed to 600 rpm and stir for 40 minutes to obtain a calcium-zinc composite heat stabilizer.
[0019] The auxiliary stabilizer includes 1 part of β-diketone, 3 parts of modified organic acid intercalated hydrotalcite and 2 parts of modified silicon dioxide; the preparation steps of the modified organic acid intercalated hydrotalcite are as follows: S1): Take 10g of expanded vermiculite, place it in 100ml of deionized water, high-speed shear at 15000rpm for 1h, then add 10ml of 0.2mol / L nitric acid solution, react in a 95℃ oil bath for 8h, perform solid-liquid separation, dry the separated silicon dioxide for later use, and collect the supernatant; S2): Take the supernatant collected in S1, add 10g zinc nitrate and 2g lanthanum nitrate, and then ultrasonicate and stir to obtain a nitrate solution; take 5g cinnamic acid and dissolve it in 50ml anhydrous ethanol, then mix 20ml of 0.5mol / L sodium hydroxide solution and 30ml of 0.05mol / L sodium bicarbonate solution, and drop it into the above nitrate solution. After the dropwise addition, centrifuge to take out the precipitate, wash it with deionized water until neutral, place it in 100ml deionized water, ultrasonicate it, and transfer it to a high-pressure reactor for hydrothermal reaction, react at 180°C for 8h, filter, wash and dry it to obtain an organic acid intercalated hydrotalcite; S3): Take S2 organic acid intercalated hydrotalcite and place it in deionized water for ultrasonic treatment, add sodium dodecyl sulfate, stir at 60°C for 2h, filter and wash, grind to obtain modified organic acid intercalated hydrotalcite; wherein the amount of the modifier is 4wt% of the organic acid intercalated hydrotalcite.
[0020] The preparation steps of modified silicon dioxide include: taking the dried silicon dioxide in S1 and placing it in a KH550 alcohol solution for ultrasonic dispersion for 30 minutes, then heating it to 80°C for reaction for 8 hours, vacuum filtering, washing and drying, placing it in a tetrahydrofuran solvent, adding maleic anhydride and mixing evenly, mechanically stirring at 90°C for 3 hours, continuing to heat to 160°C, adding pentaerythritol and reacting for 2 hours, rotary evaporating to remove tetrahydrofuran, washing and drying, and obtaining modified silicon dioxide; wherein the molar ratio of KH550, maleic anhydride and pentaerythritol is 1:1:1; the amount of KH550 is 4wt% of silicon dioxide; and the material-liquid ratio of silicon dioxide to tetrahydrofuran solvent is 1g:50ml.
[0021] Example 2: A method for preparing an environmentally friendly calcium-zinc composite heat stabilizer, comprising the following steps: Take 12 parts of auxiliary stabilizer and 3 parts of zeolite, mix them, stir at 100 rpm for 10 minutes, add 3 parts of phosphite and 6 parts of epoxidized soybean oil, increase the speed to 400 rpm, continue stirring for 10 minutes, then add 20 parts of zinc stearate and 30 parts of calcium stearate, increase the speed to 600 rpm and stir for 40 minutes to obtain a calcium-zinc composite heat stabilizer.
[0022] The auxiliary stabilizer includes 1 part of β-diketone, 3 parts of modified organic acid intercalated hydrotalcite and 2 parts of modified silicon dioxide; the preparation steps of the modified organic acid intercalated hydrotalcite are as follows: S1): Take 10g of expanded vermiculite, place it in 100ml of deionized water, high-speed shear at 15000rpm for 1h, then add 10ml of 0.2mol / L nitric acid solution, react in a 95℃ oil bath for 8h, perform solid-liquid separation, dry the separated silicon dioxide for later use, and collect the supernatant; S2): Take the supernatant collected in S1, add 10g zinc nitrate and 2g lanthanum nitrate, and then ultrasonicate and stir to obtain a nitrate solution; take 5g cinnamic acid and dissolve it in 50ml anhydrous ethanol, then mix 20ml of 0.5mol / L sodium hydroxide solution and 30ml of 0.05mol / L sodium bicarbonate solution, and drop it into the above nitrate solution. After the dropwise addition, centrifuge to take out the precipitate, wash it with deionized water until neutral, place it in 100ml deionized water, ultrasonicate it, and transfer it to a high-pressure reactor for hydrothermal reaction, react at 180°C for 8h, filter, wash and dry it to obtain an organic acid intercalated hydrotalcite; S3): Take S2 organic acid intercalated hydrotalcite and place it in deionized water for ultrasonic treatment, add sodium dodecyl sulfate, stir at 60°C for 2h, filter and wash, grind to obtain modified organic acid intercalated hydrotalcite; wherein the amount of the modifier is 4wt% of the organic acid intercalated hydrotalcite.
[0023] The preparation steps of modified silicon dioxide include: taking the dried silicon dioxide in S1 and placing it in a KH550 alcohol solution for ultrasonic dispersion for 30 minutes, then heating it to 80°C for reaction for 8 hours, vacuum filtering, washing and drying, placing it in a tetrahydrofuran solvent, adding maleic anhydride and mixing evenly, mechanically stirring at 90°C for 3 hours, continuing to heat to 160°C, adding pentaerythritol and reacting for 2 hours, rotary evaporating to remove tetrahydrofuran, washing and drying, and obtaining modified silicon dioxide; wherein the molar ratio of KH550, maleic anhydride and pentaerythritol is 1:1:1; the amount of KH550 is 4wt% of silicon dioxide; and the material-liquid ratio of silicon dioxide to tetrahydrofuran solvent is 1g:50ml.
[0024] Embodiment 3: A method for preparing an environmentally friendly calcium-zinc composite heat stabilizer, comprising the following steps: Take 15 parts of auxiliary stabilizer and 3 parts of zeolite, mix them, stir at 100 rpm for 10 minutes, add 3 parts of phosphite and 8 parts of epoxidized soybean oil, increase the speed to 400 rpm, continue stirring for 10 minutes, then add 20 parts of zinc stearate and 30 parts of calcium stearate, increase the speed to 600 rpm and stir for 40 minutes to obtain a calcium-zinc composite heat stabilizer.
[0025] The auxiliary stabilizer includes 1 part of β-diketone, 3 parts of modified organic acid intercalated hydrotalcite and 3 parts of modified silicon dioxide; the preparation steps of the modified organic acid intercalated hydrotalcite are as follows: S1): Take 10g of expanded vermiculite, place it in 100ml of deionized water, high-speed shear at 15000rpm for 1h, then add 10ml of 0.2mol / L nitric acid solution, react in a 95℃ oil bath for 8h, perform solid-liquid separation, dry the separated silicon dioxide for later use, and collect the supernatant; S2): Take the supernatant collected in S1, add 10g zinc nitrate and 2g lanthanum nitrate, and then ultrasonicate and stir to obtain a nitrate solution; take 5g cinnamic acid and dissolve it in 50ml anhydrous ethanol, then mix 20ml of 0.5mol / L sodium hydroxide solution and 30ml of 0.05mol / L sodium bicarbonate solution, and drop it into the above nitrate solution. After the dropwise addition, centrifuge to take out the precipitate, wash it with deionized water until neutral, place it in 100ml deionized water, ultrasonicate it, and transfer it to a high-pressure reactor for hydrothermal reaction, react at 180°C for 8h, filter, wash and dry it to obtain an organic acid intercalated hydrotalcite; S3): Take S2 organic acid intercalated hydrotalcite and place it in deionized water for ultrasonic treatment, add sodium dodecyl sulfate, stir at 60°C for 2h, filter and wash, grind to obtain modified organic acid intercalated hydrotalcite; wherein the amount of the modifier is 4wt% of the organic acid intercalated hydrotalcite.
[0026] The preparation steps of modified silicon dioxide include: taking the dried silicon dioxide in S1 and placing it in a KH550 alcohol solution for ultrasonic dispersion for 30 minutes, then heating it to 80°C for reaction for 8 hours, vacuum filtering, washing and drying, placing it in a tetrahydrofuran solvent, adding maleic anhydride and mixing evenly, mechanically stirring at 90°C for 3 hours, continuing to heat to 160°C, adding pentaerythritol and reacting for 2 hours, rotary evaporating to remove tetrahydrofuran, washing and drying, and obtaining modified silicon dioxide; wherein the molar ratio of KH550, maleic anhydride and pentaerythritol is 1:1:1; the amount of KH550 is 4wt% of silicon dioxide; and the material-liquid ratio of silicon dioxide to tetrahydrofuran solvent is 1g:50ml.
[0027] Comparative Example 1: Comparative Example 1 refers to Example 3, except that the modification treatment of hydrotalcite is removed. The specific steps are as follows: Take 15 parts of auxiliary stabilizer and 3 parts of zeolite, mix them, stir at 100 rpm for 10 minutes, add 3 parts of phosphite and 8 parts of epoxidized soybean oil, increase the speed to 400 rpm, continue stirring for 10 minutes, then add 20 parts of zinc stearate and 30 parts of calcium stearate, increase the speed to 600 rpm and stir for 40 minutes to obtain a calcium-zinc composite heat stabilizer.
[0028] The auxiliary stabilizer includes 1 part of β-diketone, 3 parts of organic acid intercalated hydrotalcite and 3 parts of modified silicon dioxide; the preparation steps of the organic acid intercalated hydrotalcite are as follows: S1): Take 10g of expanded vermiculite, place it in 100ml of deionized water, high-speed shear at 15000rpm for 1h, then add 10ml of 0.2mol / L nitric acid solution, react in a 95℃ oil bath for 8h, perform solid-liquid separation, dry the separated silicon dioxide for later use, and collect the supernatant; S2): Take the supernatant collected in S1, add 10g zinc nitrate and 2g lanthanum nitrate, and then ultrasonicate and stir to obtain a nitrate solution; take 5g cinnamic acid and dissolve it in 50ml anhydrous ethanol, then mix 20ml of 0.5mol / L sodium hydroxide solution and 30ml of 0.05mol / L sodium bicarbonate solution, and drop it into the above nitrate solution. After the dropwise addition, centrifuge to take out the precipitate, wash it with deionized water until neutral, place it in 100ml deionized water, ultrasonicate it, and transfer it to a high-pressure reactor for hydrothermal reaction, react at 180°C for 8h, filter, wash and dry it to obtain an organic acid intercalated hydrotalcite; The preparation steps of modified silicon dioxide include: taking the dried silicon dioxide in S1 and placing it in a KH550 alcohol solution for ultrasonic dispersion for 30 minutes, then heating it to 80°C for reaction for 8 hours, vacuum filtering, washing and drying, placing it in a tetrahydrofuran solvent, adding maleic anhydride and mixing evenly, mechanically stirring at 90°C for 3 hours, continuing to heat to 160°C, adding pentaerythritol and reacting for 2 hours, rotary evaporating to remove tetrahydrofuran, washing and drying, and obtaining modified silicon dioxide; wherein the molar ratio of KH550, maleic anhydride and pentaerythritol is 1:1:1; the amount of KH550 is 4wt% of silicon dioxide; and the material-liquid ratio of silicon dioxide to tetrahydrofuran solvent is 1g:50ml.
[0029] Comparative Example 2: Comparative Example 2 refers to Example 3, except that zinc nitrate and lanthanum nitrate are not added to the modified organic acid intercalated hydrotalcite, and specifically comprises the following steps: Take 15 parts of auxiliary stabilizer and 3 parts of zeolite, mix them, stir at 100 rpm for 10 minutes, add 3 parts of phosphite and 8 parts of epoxidized soybean oil, increase the speed to 400 rpm, continue stirring for 10 minutes, then add 20 parts of zinc stearate and 30 parts of calcium stearate, increase the speed to 600 rpm and stir for 40 minutes to obtain a calcium-zinc composite heat stabilizer.
[0030] The auxiliary stabilizer includes 1 part of β-diketone, 3 parts of modified organic acid intercalated hydrotalcite and 3 parts of modified silicon dioxide; the preparation steps of the modified organic acid intercalated hydrotalcite are as follows: S1): Take 10g of expanded vermiculite, place it in 100ml of deionized water, high-speed shear at 15000rpm for 1h, then add 10ml of 0.2mol / L nitric acid solution, react in a 95℃ oil bath for 8h, perform solid-liquid separation, dry the separated silicon dioxide for later use, and collect the supernatant; S2): Take 5g of cinnamic acid and dissolve it in 50ml of anhydrous ethanol, then mix 20ml of 0.5mol / L sodium hydroxide solution and 30ml of 0.05mol / L sodium bicarbonate solution, and add it dropwise to the supernatant collected in S1. After the addition is completed, centrifuge to remove the precipitate, wash it with deionized water until it is neutral, place it in 100ml of deionized water and ultrasonicate it, then transfer it to a high-pressure reactor for hydrothermal reaction, react at 180℃ for 8h, filter, wash and dry it to obtain organic acid intercalated hydrotalcite; S3): Take S2 organic acid intercalated hydrotalcite and place it in deionized water for ultrasonic treatment, add sodium dodecyl sulfate, stir at 60°C for 2h, filter and wash, grind to obtain modified organic acid intercalated hydrotalcite; wherein the amount of the modifier is 4wt% of the organic acid intercalated hydrotalcite.
[0031] The preparation steps of modified silicon dioxide include: taking the dried silicon dioxide in S1 and placing it in a KH550 alcohol solution for ultrasonic dispersion for 30 minutes, then heating it to 80°C for reaction for 8 hours, vacuum filtering, washing and drying, placing it in a tetrahydrofuran solvent, adding maleic anhydride and mixing evenly, mechanically stirring at 90°C for 3 hours, continuing to heat to 160°C, adding pentaerythritol and reacting for 2 hours, rotary evaporating to remove tetrahydrofuran, washing and drying, and obtaining modified silicon dioxide; wherein the molar ratio of KH550, maleic anhydride and pentaerythritol is 1:1:1; the amount of KH550 is 4wt% of silicon dioxide; and the material-liquid ratio of silicon dioxide to tetrahydrofuran solvent is 1g:50ml.
[0032] Comparative Example 3: Comparative Example 3 refers to Example 3, except that modified silicon dioxide is not added. The specific steps are as follows: Take 15 parts of auxiliary stabilizer and 3 parts of zeolite, mix them, stir at 100 rpm for 10 minutes, add 3 parts of phosphite and 8 parts of epoxidized soybean oil, increase the speed to 400 rpm, continue stirring for 10 minutes, then add 20 parts of zinc stearate and 30 parts of calcium stearate, increase the speed to 600 rpm and stir for 40 minutes to obtain a calcium-zinc composite heat stabilizer.
[0033] The auxiliary stabilizer includes 1 part of β-diketone and 3 parts of modified organic acid intercalated hydrotalcite; the preparation steps of the modified organic acid intercalated hydrotalcite are as follows: S1): Take 10g of expanded vermiculite, place it in 100ml of deionized water, high-speed shear at 15000rpm for 1h, add 10ml of 0.2mol / L nitric acid solution, react in a 95℃ oil bath for 8h, perform solid-liquid separation, and collect the supernatant; S2): Take the supernatant collected in S1, add 10g zinc nitrate and 2g lanthanum nitrate, and then ultrasonicate and stir to obtain a nitrate solution; take 5g cinnamic acid and dissolve it in 50ml anhydrous ethanol, then mix 20ml of 0.5mol / L sodium hydroxide solution and 30ml of 0.05mol / L sodium bicarbonate solution, and drop it into the above nitrate solution. After the dropwise addition, centrifuge to take out the precipitate, wash it with deionized water until neutral, place it in 100ml deionized water, ultrasonicate it, and transfer it to a high-pressure reactor for hydrothermal reaction, react at 180°C for 8h, filter, wash and dry it to obtain an organic acid intercalated hydrotalcite; S3): Take S2 organic acid intercalated hydrotalcite and place it in deionized water for ultrasonic treatment, add sodium dodecyl sulfate, stir at 60°C for 2h, filter and wash, grind to obtain modified organic acid intercalated hydrotalcite; wherein the amount of the modifier is 4wt% of the organic acid intercalated hydrotalcite.
[0034] Application example: The calcium-zinc composite heat stabilizer prepared in Examples 1-3 and Comparative Examples 1-3 is used in plastic processing, and the specific steps are as follows: Take 3 parts of calcium zinc composite heat stabilizer and mix it with 50 parts of plasticizer DOP, ultrasonically disperse it, add 50 parts of PVC paste resin and 50 parts of PVC resin powder, stir until fully mixed, evenly spread it on a long glass plate to form a film with a thickness of about 1 mm, and heat it in an oven at 120°C for 30 min to plasticize and form a sample; the addition of the calcium zinc composite heat stabilizer prepared in Example 1-3 and Comparative Example 1-3 is recorded as Sample 1, Sample 2, Sample 3, Sample 4, Sample 5, and Sample 6 in sequence for subsequent experiments.
[0035] Detection experiment 1. Thermal aging oven test: According to GB / T9349, the oven temperature is pre-set to 180°C, and samples 1-6 prepared in the application example are cut into 15×15mm 2 Place the square pieces neatly on the aluminum foil in the enamel tray. After the temperature in the oven stabilizes, put the enamel tray in. Take out the sample every 5 minutes to observe the color change. The time when the square piece completely turns black is taken as the complete aging time of the square piece.
[0036] 2. Congo red test: According to GB / T2917.1, take samples 1-6 prepared in the application example, cut them into uniform small particles, put them in the test tube of the Congo red test instrument, and immerse the samples in the test tube completely in a 180℃ oil bath to start timing. When the Congo red test paper turns blue, stop timing, which is the static thermal stability time.
[0037]
[0038] Conclusion: According to the above experimental data, the calcium zinc heat stabilizer prepared in Example 3 has a good heat stabilization effect in PVC processing, and the prepared PVC has excellent heat stabilization effect; Comparative Example 1 does not modify the hydrotalcite, which reduces the compatibility of the hydrotalcite with PVC and reduces the heat stabilization effect of PVC; Comparative Example 2 does not add zinc and lanthanum, which has a certain effect on the heat stability of PVC; Comparative Example 3 does not add modified silica, which changes the compounding system and has a great impact. Therefore, based on the above data analysis, Example 3 can achieve the best synergistic effect and improve long-term thermal stability compared with the compounding combination of each raw material in the other experiments.
[0039] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An environmentally friendly calcium-zinc composite heat stabilizer, characterized in that: The environmentally friendly calcium-zinc composite heat stabilizer comprises the following raw materials by weight: 10-20 parts of zinc stearate, 20-30 parts of calcium stearate, 10-15 parts of auxiliary stabilizer, 5-8 parts of plasticizer, 1-5 parts of antioxidant, and 2-5 parts of filler.
2. An environmentally friendly calcium-zinc composite heat stabilizer according to claim 1, characterized in that: The auxiliary stabilizer includes beta-diketone, modified organic acid intercalated hydrotalcite and modified silica, and the mass ratio of beta-diketone, modified organic acid intercalated hydrotalcite and modified silica is 1:3:(1-3).
3. An environmentally friendly calcium-zinc composite heat stabilizer according to claim 1, characterized in that: The preparation steps of the modified organic acid intercalated hydrotalcite include: S1): Take expanded vermiculite, place it in deionized water, add nitric acid solution after high-speed shearing, react in a 95°C oil bath for 8-12 hours, perform solid-liquid separation, dry the separated silicon dioxide for later use, and collect the supernatant; S2): Take the supernatant collected in S1, add zinc nitrate and lanthanum nitrate, and then sonicate and stir to obtain a nitrate solution; dissolve the organic acid in anhydrous ethanol, mix the sodium hydroxide solution and the sodium bicarbonate solution, and dropwise add the nitrate solution. After the dropwise addition, centrifuge to take out the precipitate, wash it with deionized water until it is neutral, place it in deionized water with sonication, perform hydrothermal reaction, react at 120-180°C for 8-12h, filter, wash, and dry to obtain an organic acid intercalated hydrotalcite; S3): Take S2 organic acid intercalated hydrotalcite and place it in deionized water for ultrasonic treatment, add a modifier, stir it at 60°C for 2-3h, filter and wash it, grind it, and obtain a modified organic acid intercalated hydrotalcite.
4. An environmentally friendly calcium-zinc composite heat stabilizer according to claim 1, characterized in that: The preparation steps of modified silica include: taking the dried silica prepared in S1 and placing it in a KH550 alcohol solution for ultrasonic dispersion for 30-40 minutes, then heating it to 80°C for reaction for 8-10 hours, vacuum filtering, washing and drying, placing it in a tetrahydrofuran solvent, adding maleic anhydride and mixing evenly, mechanically stirring at 70-90°C for 3-5 hours, continuing to heat to 160°C, adding pentaerythritol and reacting for 2 hours, rotary evaporating to remove tetrahydrofuran, washing and drying, and obtaining modified silica.
5. An environmentally friendly calcium-zinc composite heat stabilizer according to claim 3, characterized in that: The organic acid in S2 is any one of itaconic acid, maleic acid, cinnamic acid and citric acid.
6. An environmentally friendly calcium-zinc composite heat stabilizer according to claim 3, characterized in that: The modifier in S3 is any one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium stearate and sodium citrate.
7. An environmentally friendly calcium-zinc composite heat stabilizer according to claim 4, characterized in that: The molar ratio of KH550, maleic anhydride and pentaerythritol is 1:1:1, and the amount of KH550 used is 4-5wt% of silica.
8. An environmentally friendly calcium-zinc composite heat stabilizer according to claim 1, characterized in that: The filler is one or more combinations of zeolite, talc, zinc carbonate and calcium carbonate.
9. A method for preparing the environmentally friendly calcium-zinc composite heat stabilizer according to any one of claims 1 to 8, characterized in that: The following steps are involved: The auxiliary stabilizer and filler are mixed, stirred at a speed of 100-200 rpm for 10-30 minutes, antioxidants and plasticizers are added, the speed is increased to 300-400 rpm, stirring is continued for 5-10 minutes, zinc stearate and calcium stearate are added, the speed is increased to 400-600 rpm and stirring is continued for 30-40 minutes to obtain a calcium-zinc composite heat stabilizer.
Citation Information
Cited By
Compounding method of PVC (polyvinyl chloride) environment-friendly stabilizer
CN120310156A
A compounding method for PVC environmentally friendly stabilizers
CN120310156B
HPVC power cable protection pipe and preparation method thereof
CN120399370A
Preparation method of modified calcium-zinc stabilizer for SPC
CN120718340A
Preparation method of modified calcium-zinc stabilizer for SPC
CN120718340B
